50 success classics : your shortcut to the most important ideas on motivation, wealth, and success - Butler-Bowdon, Tom (Boston : Nicholas Brealey Publishing, 2017)
Summarizes and interprets fifty influential books on success, wealth creation, and achievement.
Includes bibliographical references.
Keywords: Success -- Quotations, maxims, etc; Self-actualization (Psychology).; Motivation (Psychology).